Environmental DNA Sampling Informs Fish Eradication Efforts: Case Studies and Lessons Learned. (2nd April 2020) - Carim, K. J.; Bean, N. J.; Connor, J. M.; Baker, W. P.; Jaeger, M.; Ruggles, M. P.; McKelvey, K. S.; Franklin, T. W.; Young, M. K.; Schwartz, M. K.
Abstract: Worldwide, freshwater ecosystems are threatened by invasive species, resulting in adverse effects on infrastructure, economy, recreation, and native aquatic communities. In stream settings, chemical piscicides can be an effective tool for eradicating invasive fishes. However, chemical treatments are expensive and time consuming, and they do not discriminate between invasive and native species in a system. Therefore, managers would ideally limit treatment to only the area occupied by the invasive species. Because traditional survey methods may not accurately detect individuals in low abundance (e.g., at the edge of their distribution, or following an eradication effort), chemical treatments may be applied more broadly and more often than is necessary to ensure complete coverage. Furthermore, inadequate posttreatment sampling can fail to detect survivors of a treatment. As a result, managers may erroneously conclude that eradication was successful, leaving the ecosystem vulnerable to reestablishment by the invader. More sensitive sampling tools should allow for more precise definition of the treatment area and more accurate evaluation of project success. This would reduce project costs and overall effects on native species. Here, we illustrate how environmental DNA (eDNA) sampling addressed these challenges through three case studies, each of which used eDNA sampling to inform the removal of Brook Trout Salvelinus fontinalis in small streams. We found that eDNA methods can be informative throughout all stages of eradication projects in stream settings. It can assist with delimiting the population prior to treatment, provide detailed location data on surviving target individuals, and serve as an efficient and relatively inexpensive monitoring tool to assess long‐term treatment efficacy. When combined with traditional survey tools, such as electrofishing, eDNA sampling may help reduce the size and number of treatments that are necessary to reach project goals. This translates directly to increased efficacy of treatments, reduced labor and cost, and reduced adverse effects on the native community.